Immunization and media coverage in Italy: an eleven-year analysis (2007-17). Issue 10 (3rd October 2018) - Odone, A.; Tramutola, V.; Morgado, M.; Signorelli, C.
ABSTRACT: Immunization polices in Italy has recently reached important milestones, including the approval of the National Immunization Prevention Plan and of a new law mandatory immunization; this stimulating a lively debate at the scientific, political and societal-level, reflected on the media. We applied a model previously published to quantitatively and qualitatively assess media coverage on vaccines and immunization-related topics on the most read Italian newspaper, "Corriere della Sera", over an 11-year study period (2007-2017). We retrieved relevant key words and articles, reported on included articles' topic, position, approach to immunization and on other selected indicators' summary statistics, temporal trends and correspondence with key epidemiological and policy events. Over the study period the quote "vaccin*" was mentioned on average 325 times per year; with an increase of 150% after the approval of the new law on mandatory immunization in 2017. In the same year, on average, two first-page articles per week were published on the topic. We report a clear association between key events (i.e the H1N1 influenza pandemic, the "Fluad case", the approval of the new law on mandatory immunization) and their media coverage. Overall, 84% of articles had a positive attitude towards immunization, this share decreasing to 79% when only considering articles published after the approval of the law on mandatory vaccination. Media play a crucial role in channelling health-related information and significantly influence health behaviours. We urge public institutions, health authorities and the scientific community not to underestimate the opportunity to monitor media coverage on key healthcare topics and to convey evidence-based health education messages through the media.